2015
DOI: 10.1523/jneurosci.4315-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking Proteolytic Activity for Adult Visual Cortex Plasticity by the Removal of Lynx1

Abstract: Experience-dependent cortical plasticity declines with age. At the molecular level, experience-dependent proteolytic activity of tissue plasminogen activator (tPA) becomes restricted in the adult brain if mice are raised in standard cages. Understanding the mechanism for the loss of permissive proteolytic activity is therefore a key link for improving function in adult brains. Using the mouse primary visual cortex (V1) as a model, we demonstrate that tPA activity in V1 can be unmasked following 4 d of monocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…In the visual cortex, neuroserpin expression is increased during the critical period and decreased following monocular deprivation (Wannier-Morino et al 2003). Removal of Lynx1, a negative regulator of adult plasticity, leads to experience-dependent elevation of tPA and increased plasticity, a process blocked by administration of neuroserpin (Bukhari et al 2015). In addition to this direct evidence linking neuroserpin to synaptic function, translational data from schizophrenic patients, a disorder characterized by improper synaptic function, showed dysregulation of neuroserpin (Hakak et al 2001;Vawter et al 2004;Brennand et al 2011;Wen et al 2014), and mice with dysregulated expression of neuroserpin show selective reduction of locomotor activity in novel environments, anxiety-like response on the O-maze, and neophobic response to novel objects (Madani et al 2003).…”
mentioning
confidence: 99%
“…In the visual cortex, neuroserpin expression is increased during the critical period and decreased following monocular deprivation (Wannier-Morino et al 2003). Removal of Lynx1, a negative regulator of adult plasticity, leads to experience-dependent elevation of tPA and increased plasticity, a process blocked by administration of neuroserpin (Bukhari et al 2015). In addition to this direct evidence linking neuroserpin to synaptic function, translational data from schizophrenic patients, a disorder characterized by improper synaptic function, showed dysregulation of neuroserpin (Hakak et al 2001;Vawter et al 2004;Brennand et al 2011;Wen et al 2014), and mice with dysregulated expression of neuroserpin show selective reduction of locomotor activity in novel environments, anxiety-like response on the O-maze, and neophobic response to novel objects (Madani et al 2003).…”
mentioning
confidence: 99%
“…If nicotinic cholinergic signaling could regulate critical period plasticity, then how would then plasticity become severely restricted in adulthood even in the remaining presence of robust basal forebrain cholinergic innervation? Here we introduce Lynx1, an allosteric cholinergic modulator that increases into adulthood after critical period, and review its contribution to regulate functional and structural plasticity in the V1 (Bukhari et al, 2015; Morishita et al, 2010; Sajo et al, 2016). The discovery of the role of nicotinic cholinergic modulator Lynx1 as a plasticity regulator has given light to a new perspective – the brain is intrinsically plastic even in adulthood, but is actively masked by molecular plasticity “brakes” (Bavelier et al, 2010).…”
Section: Regulation Of Critical Period Closure By Lynx1 An Endogementioning
confidence: 99%
“…Assessment of OD plasticity in Lynx1 knockout (KO) mice found that removal of Lynx1 prolongs heightened V1 plasticity into adulthood but not without the possibility of “re-masking” the plasticity through active pharmacological blockade of nAChR signaling. In the follow up study, it was further examined to what extent elevated OD plasticity in adult Lynx1KO mice reflects juvenile forms of plasticity (Bukhari et al, 2015). In juvenile mice, the OD shift after 4 days of MD is mediated primarily by a decrease of deprived contralateral eye response in the V1(Sato and Stryker, 2008).…”
Section: Regulation Of Critical Period Closure By Lynx1 An Endogementioning
confidence: 99%
See 2 more Smart Citations